Etiam realis scientia : Petrus Aureolis konzeptualistische Transzendentalienlehre vor dem Hintergrund seiner Kritik am Formalitätenrealismus - Gaus, Caroline (Studien und Texte zur Geistesgeschichte des Mittelalters ;, 2008)
Research on the medieval doctrine of the transcendentals is characterized by one debate: its characteristic peculiarity vs its structural correspondence to the modern concept of transcendentality. This study on Peter Aureol's (1322) doctrine of transcendentals offers a contribution to that discussion.